The Sustainability Level of The Rice Farming in The Peatland at The Kapuas Regency, Central Kalimantan - Jhon Wardie; Tri Yuliana Eka Sintha (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
The research aims to analyse the level of sustainability and the level of household income in the farming of rice on the peatland. The research location was determined by purposive sampling in Terusan Karya Village, Bataguh District, Kapuas Regency. The simple random sampling method was taken on 50 farmer household served as respondent. The data were collected in the form of primary and secondary data. To achieve the first research objective, it was conducted by an analysis of sustainability indicators of farming using Likert Scale system. The index of farming sustainability includes biophysical and socio-economic aspects in the rice farming on peatland. Meanwhile, to achieve the purpose of the second research, it was operated by using a simple tabulation to measure the level of farmer household income. The result of the analysis showed that farming sustainability of rice in the peatland found index by 76.10 percent, which means that the level of farming sustainability is a good category or highly sustainable. The result of the analysis of farm household income was 16.9 million rupiahs, which means that the farm household income has been categorized as good.  JEL Classification: D10, Q01, Q12